Laparoscopic appendectomy at the Hospital Nacional Daniel A. Carrion - Callao - Taboada, Martín (1998)
Our initial experience with laparoscopic appendectomy in the management of patients with acute appendicitis at the Hospital Nacional Daniel Alcides Carrion, between January 1997 and December 1997, is reported. A total of 35 laparoscopic procedures, were performed. The median age was 23,8 years (range, 10 to 47 years) with 57,1% males (n = 20) and 42,9% females (n = 15). 10 patients (28,5%) had perforated appendicitis; 5 patients (14,2%) had minor intraoperative complications, none of them modified final results. Trochar wound infection was present in three patients. The median postoperative length of stay was 2 days for non complicated and 7 days for complicated patients. Length of time for the procedure was, in most of cases, adequate.